Levelized cost of energy of hybrid concentrating photovoltaic-thermal systems based on nanofluid spectral filtering. (October 2021) - Rodrigues Fernandes, Marcelo; Schaefer, Laura A.
Highlights: An LCOE analysis was created to assess the feasibility of spectral filtering systems. Hybrid Si and GaAs systems were compared to a conventional parabolic trough system. The hybrid systems can be economically viable depending on the solar multiple. Abstract: The field of concentrating photovoltaic-thermal (CPV-T) systems based on nanofluid spectral filtering has advanced significantly in the past decade. However, there is still a need to perform economic feasibility analyses for these systems. In this work, an assessment of the cost of implementation of CPV-T power plants using the spectral-splitting technique was performed. Three types of solar power plant were analyzed, including a purely thermal parabolic trough, a hybrid Si-based, and a hybrid GaAs-based power plant. The levelized cost of energy (LCOE) algorithm included inputs obtained from random variables to obtain LCOE values and energy generation for each type of power plant as a probability distribution. The results show that a purely thermal parabolic trough system has a minimum LCOE of 13.29 ¢/kWh at a solar multiple of 1.75, while the hybrid Si and hybrid GaAs power plants had a minimum LCOE of 17.83 ¢/kWh at a solar multiple of 2.5, and 14.50 ¢/kWh at a solar multiple of 3. The results in this work demonstrate that spectral-splitting CPV-T power plants can achieve energy costs comparable to conventional parabolic power plants depending on the solar multiple, solar cell material, and technical and financial variables.